2021
DOI: 10.1016/j.jneuroim.2021.577597
|View full text |Cite
|
Sign up to set email alerts
|

Altered distributions and functions of natural killer T cells and γδ T cells in neonates with neonatal encephalopathy, in school-age children at follow-up, and in children with cerebral palsy

Abstract: We enumerated conventional and innate lymphocyte populations in neonates with neonatal encephalopathy (NE), school-age children post-NE, children with cerebral palsy and age-matched controls. Using flow cytometry, we demonstrate alterations in circulating T, B and natural killer cell numbers. Invariant natural killer T cell and Vδ2 + γδ T cell numbers and frequencies were strikingly higher in neonates with NE, children post-NE and children with cerebral palsy compared to age-matched controls, whereas mucosal-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Neonatal B cells lack antigenic exposure, furthermore they have impaired antibody production and an incomplete surface immunoglobulin repertoire ( Li et al., 2017 ). Our group reported that circulating B cell numbers are higher in neonates and school-age children with NE and cerebral palsy compared to age-matched control subjects ( Taher et al., 2021 ). B cell frequencies are higher in the injured hemisphere of the brain compared to the uninjured hemisphere 7 days after HI in a mouse model of HI-induced preterm brain injury, whereas T cells are found as soon as 3 days after HI ( Nazmi et al., 2018 ).…”
Section: B Lymphocytesmentioning
confidence: 91%
See 4 more Smart Citations
“…Neonatal B cells lack antigenic exposure, furthermore they have impaired antibody production and an incomplete surface immunoglobulin repertoire ( Li et al., 2017 ). Our group reported that circulating B cell numbers are higher in neonates and school-age children with NE and cerebral palsy compared to age-matched control subjects ( Taher et al., 2021 ). B cell frequencies are higher in the injured hemisphere of the brain compared to the uninjured hemisphere 7 days after HI in a mouse model of HI-induced preterm brain injury, whereas T cells are found as soon as 3 days after HI ( Nazmi et al., 2018 ).…”
Section: B Lymphocytesmentioning
confidence: 91%
“…observed that inactivation of NK cells by CD161 knockdown resulted in a decrease in brain and systemic organ atrophy and neurobehavioral deficits ( Fathali et al., 2013 ), suggesting a key role for NK cells in brain injury and multiorgan dysfunction in NE. Investigating human peripheral blood cell phenotypes, Taher and co-workers ( Taher et al., 2021 ) found that circulating NK cell frequencies are higher in neonates with NE compared to healthy neonates and these cells displayed activated phenotypes and more readily produced IFN-γ, TNF-α and granzyme B upon stimulation ex vivo .…”
Section: Natural Killer Cellsmentioning
confidence: 99%
See 3 more Smart Citations